Comparative Genomics Suggests a Taxonomic Revision of the Staphylococcus cohnii Species Complex. (12th February 2021) - Lavecchia, Anna; Chiara, Matteo; De Virgilio, Caterina; Manzari, Caterina; Pazzani, Carlo; Horner, David; Pesole, Graziano; Placido, Antonio
Abstract: Staphylococcus cohnii (SC), a coagulase-negative bacterium, was first isolated in 1975 from human skin. Early phenotypic analyses led to the delineation of two subspecies (subsp.), Staphylococcus cohnii subsp . cohnii (SCC) and Staphylococcus cohnii subsp . urealyticus (SCU). SCC was considered to be specific to humans, whereas SCU apparently demonstrated a wider host range, from lower primates to humans. The type strains ATCC 29974 and ATCC 49330 have been designated for SCC and SCU, respectively. Comparative analysis of 66 complete genome sequences—including a novel SC isolate—revealed unexpected patterns within the SC complex, both in terms of genomic sequence identity and gene content, highlighting the presence of 3 phylogenetically distinct groups. Based on our observations, and on the current guidelines for taxonomic classification for bacterial species, we propose a revision of the SC species complex. We suggest that SCC and SCU should be regarded as two distinct species: SC and SU ( Staphylococcus urealyticus ), and that two distinct subspecies, SCC and SCB (SC subsp. barensis, represented by the novel strain isolated in Bari) should be recognized within SC. Furthermore, since large-scale comparative genomics studies recurrently suggest inconsistencies or conflicts in taxonomic assignments of bacterial species, we believe that the approach proposed here might be considered for more general application.